Bacterial composition isolated from ulcers “ba dau” of soft-shelled turtles (Pelodiscus sinensis) in Nam Dinh farm and characterization of Aeromonas spp. virulence - Lan Anh, Hoang Thi; Linh, Bui Nguyen Hai; Dung, Nguyen Huu Tuan; Hue, Le Thi Thanh; Ha, Nguyen Viet; Cuong, Luong Minh; Trung, Trinh Thanh (Vietnam Journal of Biotechnology, 2021)
Pelodiscus sinensis is a widespread species of soft-shelled turtle that is commercially cultured in freshwater and prominently exploited as speciality food in Vietnam. During the cultivation, there are distinctly recurrent epidemic diseases causing economically vast damage for farmers. In this research, we carried out the isolation of microorganisms from typical ulcers “ba dau” presenting on soft-shelled turtle taken in Nam Dinh farm. The samples were inoculated on common media used for bacteria, actinomyces, fungus and yeast. Only bacteria grew on typical culture medium. Fifteen bacterial strains were isolated and identified by 16S rRNA sequence analysis. They were belonged to genera such as Acidovorax (n=1), Acinetobacter (n=1), Aeromonas (n=8), Citrobacter (n=1), Chryseobacterium (n=1), Moraxella (n=1), Paludibacterium (n=1) and Parabacteroides (n=1). In which, eight strains Aeromonas spp. were selected for further research on virulence characterization. PCR results showed that these strains possessed at least 4/7 virulence genes including aer (75%), alt (37.5%), ast (50%), ela (87.5%), exu ( 100%), hlyA (37.5%) and ser (100%). With additional tests, we confirmed the virulent expression by haemolysin (100%), protease (75%), DNAase (75%), elastase (25%) and cytotoxicity (62.5%). These results are scientific basis to establish and develop practical methods for controlling and preventing "ba dau" disease in the soft-shelled turtle in the future.